2000
DOI: 10.1152/ajpgi.2000.279.4.g806
|View full text |Cite
|
Sign up to set email alerts
|

Role of gut-enriched Krüppel-like factor in colonic cell growth and differentiation

Abstract: Cancer cells differ from normal cells in many aspects, including hyperproliferation and loss of differentiation. Recent research has focused on the role of transcription factors in regulating abnormal cell growth. Gut-enriched Krüppel-like factor (GKLF) is a newly identified eukaryotic zinc finger protein expressed extensively in the gastrointestinal tract. In the current study, we demonstrated that GKLF mRNA levels were significantly decreased in the dysplastic epithelium of the colon, including adenomatous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
102
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 26 publications
5
102
0
Order By: Relevance
“…This family comprises more than 20 members, including Sp1, Sp2, Sp3, Sp4, and various Krü ppel-like factors including the gut-enriched Krü ppel-like factor, GKLF. 51 Sp1-like factors are involved in epithelial differentiation in the colon, [52][53][54] and their expression has been shown to be perturbed in dysplastic lesions and carcinoma. 53,55 Sp1-like factors possess distinct transcriptional activities and may associate with other transcription factors and histone modifying enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This family comprises more than 20 members, including Sp1, Sp2, Sp3, Sp4, and various Krü ppel-like factors including the gut-enriched Krü ppel-like factor, GKLF. 51 Sp1-like factors are involved in epithelial differentiation in the colon, [52][53][54] and their expression has been shown to be perturbed in dysplastic lesions and carcinoma. 53,55 Sp1-like factors possess distinct transcriptional activities and may associate with other transcription factors and histone modifying enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…51 Sp1-like factors are involved in epithelial differentiation in the colon, [52][53][54] and their expression has been shown to be perturbed in dysplastic lesions and carcinoma. 53,55 Sp1-like factors possess distinct transcriptional activities and may associate with other transcription factors and histone modifying enzymes. 51,56 Their activity may be modulated by enzymatic modifications including acetylation and has been shown to be altered by histone deacetylase inhibitors such as butyrate.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, ectopic expression of Klf4 accelerates terminal differentiation, leading to premature skin-barrier acquisition 7 , whereas Klf4 deficiency prevents the terminal differentiation of colonic goblet cells 8 and the skin epithelium 9 , which leads to neonatal death 9 . These observations establish KLF4 as a stress-and differentiation-associated inhibitor of proliferation 10 , raising the possibility that KLF4 may have tumour-suppressive functions 8,11,12 .Indeed, KLF4 expression is frequently lost in various human cancer types 11,[13][14][15][16][17][18][19] . Recently, KLF4 has been shown to undergo promoter methylation and loss of heterozygosity in gastrointestinal cancer 16,17 .…”
mentioning
confidence: 95%
“…Indeed, KLF4 expression is frequently lost in various human cancer types 11,[13][14][15][16][17][18][19] . Recently, KLF4 has been shown to undergo promoter methylation and loss of heterozygosity in gastrointestinal cancer 16,17 .…”
mentioning
confidence: 99%
“…In vitro studies have suggested that GKLF plays an important role in cell proliferation and/or differentiation (Shie et al, 2000b). However, gene ablation in mice leads to a specific deficiency in the barrier function of the skin, resulting in postnatal death.…”
Section: Introductionmentioning
confidence: 99%